Tripchlorolide May Improve Spatial Cognition Dysfunction and Synaptic Plasticity after Chronic Cerebral Hypoperfusion - Zhao-Hui Yao; Xiao-li Yao; Shao-feng Zhang; Ji-chang Hu; Yong Zhang (Neural Plasticity)
Chronic cerebral hypoperfusion (CCH) is a common pathophysiological mechanism that underlies cognitive decline and degenerative processes in dementia and other neurodegenerative diseases. Low cerebral blood flow (CBF) during CCH leads to disturbances in the homeostasis of hemodynamics and energy metabolism, which in turn results in oxidative stress, astroglia overactivation, and synaptic protein downregulation. These events contribute to synaptic plasticity and cognitive dysfunction after CCH. Tripchlorolide (TRC) is an herbal compound with potent neuroprotective effects. The potential of TRC to improve CCH-induced cognitive impairment has not yet been determined. In the current study, we employed behavioral techniques, electrophysiology, Western blotting, immunofluorescence, and Golgi staining to investigate the effect of TRC on spatial learning and memory impairment and on synaptic plasticity changes in rats after CCH. Our findings showed that TRC could rescue CCH-induced spatial learning and memory dysfunction and improve long-term potentiation (LTP) disorders. We also found that TRC could prevent CCH-induced reductions in N-methyl-D-aspartic acid receptor 2B, synapsin I, and postsynaptic density protein 95 levels. Moreover, TRC upregulated cAMP-response element binding protein, which is an important transcription factor for synaptic proteins. TRC also prevented the reduction in dendritic spine density that is caused by CCH. However, sham rats treated with TRC did not show any improvement in cognition. Because CCH causes disturbances in brain energy homeostasis, TRC therapy may resolve this instability by correcting a variety of cognitive-related signaling pathways. However, for the normal brain, TRC treatment led to neither disturbance nor improvement in neural plasticity. Additionally, this treatment neither impaired nor further improved cognition. In conclusion, we found that TRC can improve spatial learning and memory, enhance synaptic plasticity, upregulate the expression of some synaptic proteins, and increase the density of dendritic spines. Our findings suggest that TRC may be beneficial in the treatment of cognitive impairment induced by CCH.